Large-Scale Field Test Study on Failure Mechanism of Non-Cohesive Landslide Dam by Overtopping - Li, Liang; Yang, Xingguo; Zhou, Jiawen; Zhang, Jieyuan; Fan, Gang (Frontiers in Earth Science, 2021)
In recent years, landslide lake disasters occur frequently in southwest mountainous areas of China. Considering the influence of dam size and discharge channel location, three large-scale field tests were carried out in a natural river to study the failure process and mechanism of non-cohesive soil landslide dam, and the process and mechanism of non-cohesive landslide dam breach were analyzed. The results show that the dam size and discharge channel location have a significant influence on the breach mechanism of the landslide dam. The dam failure process can be divided into three stages: the initiation stage, the development stage and the failure stage. When the discharge channel is located close to the bank, the width of the breach is smaller, and the volume of the residual dam body is larger. The more stable the dam body is, the longer the breach process time is, and the smaller the peak discharge is. This study can provide a scientific reference for the emergency disposal and risk assessment of landslide dam.